HBR's 10 must reads on negotiation (Harvard Business Review Press, 2019)
This book will inspire you to: control the negotiation before you enter the room; persuade others to do what you want - for their own reasons; manage emotions on both sides of the table; understand the rules of negotiating across cultures; set the stage for a healthy relationship long after the ink has dried; and identify what you can live with and when to walk away